2005
DOI: 10.1089/thy.2005.15.222
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone, the Peroxisome Proliferator-Activated Receptor-γ Agonist, Induces Antiproliferation and Redifferentiation in Human Thyroid Cancer Cell Lines

Abstract: Troglitazone is a potent agonist for the peroxisome proliferator-activated receptor-gamma (PPARgamma) that is a ligand-activated transcription factor regulating cell differentiation and growth. PPARgamma may play a role in thyroid carcinogenesis since PAX8-PPARgamma1 chromosomal translocations are commonly found in follicular thyroid cancers. We investigated the antiproliferative and redifferentiation effects of troglitazone in 6 human thyroid cancer cell lines: TPC-1 (papillary), FTC-133, FTC-236, FTC-238 (fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 46 publications
8
58
1
2
Order By: Relevance
“…These antitumor effects have also been attributed to PPARg activation. There is evidence that PPARg agonists promote cell redifferentiation, which is reflected in the upregulation of specific differentiation markers (NIS, TSH receptor, LPO, and thyroglobulin) and downregulation of a dedifferentiation marker (CD97) in thyroid cancer (Park et al 2005, Aiello et al 2006. Additional experiments are required to confirm this hypothesis with respect to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These antitumor effects have also been attributed to PPARg activation. There is evidence that PPARg agonists promote cell redifferentiation, which is reflected in the upregulation of specific differentiation markers (NIS, TSH receptor, LPO, and thyroglobulin) and downregulation of a dedifferentiation marker (CD97) in thyroid cancer (Park et al 2005, Aiello et al 2006. Additional experiments are required to confirm this hypothesis with respect to breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As the discovery of the PAX8-PPARg fusion gene in human follicular thyroid carcinoma and the demonstration of loss of PPARg transcription activity in the PAX8-PPARg fusion gene , there has been great interest in understanding the role of PPARg in the development and progression of follicular thyroid carcinoma. In vitro cell-based studies have shown that troglitazone induces antiproliferation and apoptosis in several human thyroid cell lines (Ohta et al, 2001;Park et al, 2005), but TRb PV/PV mice provide the first opportunity to address this question in vivo. The present study showed that treatment of TRb PV/PV mice in vivo with PPARg ligands inhibited thyrocyte proliferation and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists of PPARg had an antiproliferative action in six cell lines, originated from patients with papillary thyroid cancer which expressed PPARg, inducing apoptosis (Ohta et al 2001), significantly inhibited tumor growth and prevented distant metastasis of thyroid cancer in nude mice. Furthermore, it has been shown that troglitazone significantly inhibited cell growth by cell cycle arrest and apoptotic cell death (Park et al 2005). More recently, we have shown in primary cultured human anaplastic and papillary dedifferentiated thyroid cancers cells the antiproliferative effect of PPARg agonists thiazolidinediones (TZDs; Antonelli et al 2008a,b).…”
Section: Introductionmentioning
confidence: 96%